The Role of Work Engagement in Mediating Affective Commitment and Leadership Behavior on OCB at PT Askrindo - Rinafi, Rinafi; Gorda, AAN Eddy Supriyadinata (Politeknik Siber Cerdika Internasional, 2026)
Background: This study is motivated by 1) the limited implementation of harmony and loyalty as part of the AKHLAKvalues and 2) the decline in extra-role behavior among millennial employees at PT Askrindo. Objective: This research investigates the relationships between Affective Commitment (AC) and Leadership Behavior (LB) and Organizational Citizenship Behavior (OCB), as mediated by Work Engagement (WE), among millennial employees. Methods: Using a saturated sampling method, 180 millennial employees were selected through a quantitative explanatory research design. Data were collected using Likert-scale questionnaires and analyzed using SEM-PLS through SmartPLS. Results: The results indicated that AC was not significantly related to OCB (T = 1.243, p = 0.214) but was positively associated with WE (T = 3.817, p = 0.000). On the other hand, LB had a significant positive effect on OCB (T = 4.102, p = 0.000) and WE (T = 5.231, p = 0.000). Moreover, WE also had a positive effect on OCB (T = 3.654, p = 0.000). Bootstrapping analysis repeated with 5,000 samples confirmed that WE completely mediated the AC–OCB relationship (indirect effect = 0.134, T = 2.895, p = 0.004) and partially mediated the LB–OCB relationship (indirect effect = 0.202, T = 3.711, p = 0.000). Conclusion: The direct effect of affective commitment on employee OCB can be enhanced through work engagement and leadership behavior as mediating variables. This research also contributes significantly to the fields of Social Exchange Theory and Job Demands–Resources Theory by providing empirical evidence concerning employees, particularly millennials working in state-owned enterprises.